2005
DOI: 10.1243/135065005x9664
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication regime transitions at the piston ring-cylinder liner interface

Abstract: An experimental apparatus and an analytical model have been developed to investigate and determine the lubrication condition and frictional losses at the interface between a piston ring and cylinder liner. In order to obtain a solution for the lubrication condition between the piston ring and cylinder liner, the system of Reynolds and film thickness equations subject to boundary conditions were simultaneously solved. The effects of boundary and mixed lubrication conditions were implemented using the Greenwood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 19 publications
3
97
0
Order By: Relevance
“…Piston skirt and ring-pack are the primary sources of friction in the engine (around 40 per cent) with losses due to ring-pack being the largest, such that the compression rings are responsible for 4 to 5 per cent of all losses in a typical multi-cylinder IC engine. Given that 4 per cent reduction in parasitic losses translates directly to 1 per cent gain in fuel efficiency, the lack of very detailed analysis, except for a few notable contributions [1][2][3], is rather surprising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piston skirt and ring-pack are the primary sources of friction in the engine (around 40 per cent) with losses due to ring-pack being the largest, such that the compression rings are responsible for 4 to 5 per cent of all losses in a typical multi-cylinder IC engine. Given that 4 per cent reduction in parasitic losses translates directly to 1 per cent gain in fuel efficiency, the lack of very detailed analysis, except for a few notable contributions [1][2][3], is rather surprising.…”
Section: Introductionmentioning
confidence: 99%
“…At the bottom dead centre and during strokes other than power-stroke, the contact force is quite low and, with momentary cessation of entraining motion, boundary interactions are prevalent. In such instances any reduced friction from direct boundary interactions is entirely due to lubricant entrapment by squeeze film action [9] and by non-Newtonian behaviour of very thin adsorbed films at the tips of asperity pairs [2,[10][11][12]. Therefore, a detailed analysis should account for non-Newtonian frictional characteristics of the contact, as well as local deformation of surfaces and squeeze film action (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The model was validated with experimental results obtained from Furuhama and Sasaki [17]. Bolander et al [18] in his study of transition of lubrication regime in the piston ring-Liner surface found that at Dead centres, mostly boundary lubrication is present and asperityasperity contact is there at TDC. Study was experimentally validated with analytical results showed good correlation.…”
Section: Top Ring Reversal Bore Wearmentioning
confidence: 65%
“…the hardness of the material. The normal load F N and contact speed u m are respectively equal to 50 N and 300 rpm [28]. It simulate the piston ring-cylinder bore contact in mixed regime that occur near the Top Dead Center (TDC) and Bottom Dead Center (BDC) [28].…”
Section: Numerical Proceduresmentioning
confidence: 99%